KEHIDUPAN MUALLAF DI KOTA PEKANBARU - Nela Mita; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Convert life in the city of Pekanbaru. This research was conducted in the city of Pekanbaru. The purpose of this study is to determine the motive for converting to Islam and to find out how the adaptation of converts to Islam after converting to Islam. In carrying out the research, the determination of the subject was carried out using a purposive sampling technique whose criteria had been determined based on the needs of this study. Based on these criteria, 4 informants were taken as research subjects of converting life in the city of Pekanbaru. The theory used in this research is the theory of action by George Herbert Mead and the theory of adaptation by Robert K. Merton. The result of this proposed research is that the informant as a convert to Islam has the same motive for converting religion into Islam, where previously they were initially interested in Islam, they were looking for what Islam and Islamic teachings are, after which they pause for decisive action they will take and in the last stage they decide to become converts. After taking action and converting to Islam, they must adapt to the goals and methods that have been set, starting from adapting themselves, with others, their habits. Based on this research, there is no withdrawal stage, the final adaptation stage is to rebel because of the rejection of goals and methods by determining alternatives to substitute goals and methods. Keywords: Religious Conversion, Converts, Motives, Adaptation.